Perspektif Lembaga Pers Mahasiswa Unsika Terkait Kekerasan Verbal Kepada Wartawan di Lingkungan Kampus - Bevani, Friscilla Naldia; Azahra, Tyara; Widarasari, Umi (Universitas Singaperbangsa Karawang, 2023)
Verbal violence against journalists is a form of threat that cannot be avoided. The Student Press Institute (LPM) of Singaperbangsa University Karawang (Unsika) is one of the Student Activity Unit (UKM) forums which includes students who act as journalists in the campus environment. Among the members of LPM Unsika who work as journalists in the field, they are certainly not free from forms of violence that have been experienced, one of which is verbal violence that arises from certain individuals and is involved as a source or party who is the topic that will be investigated in LPM's journalistic products. Unsika. The method used in this research is a descriptive qualitative research method and emphasizes an in-depth interview process with several sources who meet the criteria for research informants. In this research, the theory used is press freedom theory. Based on the results of research that has been carried out, violence against journalists on the Unsika campus is still often found, especially during the reporting process on campus grounds. Keywords: Journalist, Verbal, Violence